Penerapan Metode Pose to Pose dalam Film Animasi 3D Edukasi Nura Sang Cahaya Harapan - Mubarok, Muhamad Husni; Nugroho, Fresy; Hasanah, Novrindah Alvi (JOURNAL OF APPLIED MULTIMEDIA AND NETWORKING, 2025)
This research aims to develop an educational 3D animation film titled "Nura the Light of Hope" by applying the Pose to Pose method as the main technique in character animation. The story focuses on the main character, Nura, a humble old lamp, which teaches moral values such as gratitude, humility, and the importance of appreciating differences. The animation production process is divided into three main stages, namely pre-production (script writing, character design, and storyboard), production (modeling, texturing, rigging, animating, rendering), and post-production (final rendering, dubbing, and editing). The results obtained show that the use of the Pose to Pose method is able to create expressive character movements and in accordance with the emotions of the story, thus supporting the delivery of educational messages effectively to children aged 7-12 years. This movie is expected to be an alternative learning media that is interesting and meaningful in the context of children's education in the digital era.